PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL UNTUK MENGUJI PERSEPSI RESIKO ADOPSI E-BANKING - Saputro, Edy Purwo; Nurdiana, Fereshti (Universitas Muhammadiyah Surakarta, 2012)
The purpose of this paper is to identify risk factors that discourage consumers fromadopting e-banking services. Perceived risk is a key construct in consumer decision making, whereaswhether this is true in e-banking market is rarely researched. An exploration of this dynamicmarket is therefore critical to develop theoretical and practical implications. The investigationuses quantitative research methods. Primary data were collected by self-administered questionnairescontaining 200 respondents are analysed through structural equation modelling. Results indicatethat the concept of perceived risk has merit in explaining consumersâ decisions on whether to usee-banking.